T, Trainer Skripsi Trainer Simulasi Penerangan Bagian Luar dan Bagian Dalam Pesawat Udara Sebagai Media Pembelajaran di SMK Penerbangan Semarang - Gunawan, Feri Adi (Edu Elektrika Journal, 2016)
Some obstacles in the process of teaching and learning in SMK Penerbangan Semarang ie from two class KPU A second class consisting of 33 students and 34 students KPU and the lack of lighting simulation trainer aircraft. Therefore we need some props that can be used to understand the learning process of students in the subject matter light aircraft. `Kind of research method used is the "Research and Development" (Research and Development / R & D). According Sugiyono (2009: 297) "method of research and development or Research and Development (R & D) is the research methods used to examine a product to produce a new product, and then test the effectiveness of the product. This study started from looking for potential and problems, limiting the problems, preparation of tools and materials, design, tool design, manufacturing process, ready for application, testing experts, due diligence tools, data analysis and conclusions. Collecting data using questionnaires. Data analysis using descriptive data analysis. ` The results of the draft in the form of light trainer aircraft by using a miniature aircraft as air planes and the control box controls, aircraft lights. There is a terminal for connecting the plane with the control box. The results of feasibility studies teachers to the trainer of the 10 indicators showed average of 86.25% said very good. The test results conducted expert on media expert, of the 10 points given statement obtained an average of 92.5% expressed very well the lighting simulation trainer aircraft. ` Results of implementation based on the questions that have been given to students indicate that students know the position, function and name of aircraft lights and can determine the sequence of the lights were operated during take off and landing aircraft. Based on the research conclusions, then there are some suggestions including lighting simulation trainer aircraft is expected to have further development with emphasis on the lights inside the aircraft. Neatness is further enhanced cable. Trainer when more compact size would be more practical.